Jak/STAT and PI3K signaling pathways have both common and distinct roles in IL‐7‐mediated activities in human CD8+ T cells. Issue 1 (26th September 2013) - Crawley, Angela M.; Vranjkovic, Agatha; Faller, Elliott; McGuinty, Michaeline; Busca, Aurelia; Burke, Stephanie C.; Cousineau, Sophie; Kumar, Ashok; MacPherson, Paul A.; Angel, Jonathan B.
Abstract : Inhibition of Jak activation in CD8 T cells reduced IL‐7‐induced Bcl‐2, and perforin production, while inhibition of either Jak/STAT or PI3K pathways reduced glucose uptake and proliferation. Abstract : IL‐7 plays an important role in T cell survival, function, and memory cell development, yet the role of cytokine signaling pathways in these processes has not been fully elucidated. Moreover, the underlying mechanisms for the observed impairment of IL‐7 activity in diseases, such as HIV infection, breast cancer, and autoimmunity, are not well understood. It was therefore hypothesized that IL‐7‐induced signaling molecules could be linked with distinct IL‐7‐associated activities. To address this, the activation and functional associations of IL‐7‐induced signaling pathways, specifically antigen‐independent activities that are relevant to T cell homeostasis, were examined. Low concentrations of IL‐7 (100 pg/ml) are capable of activating the Jak‐STAT and PI3K signaling pathways, whereas higher concentrations (500–1000 pg/ml) were required to induce Bcl‐2 production and glucose uptake. Even higher concentrations of IL‐7 (10, 000 pg/ml) were needed to induce cell proliferation and intracellular accumulation of perforin. Inhibition of Jak activation reduced IL‐7‐induced Bcl‐2 and perforin production, whereas inhibition of Jak/STAT or PI3K pathways reduced glucose uptake and proliferation. This study suggests a complex control of IL‐7‐associated activities in the absence of antigen stimulation. These data may provide insights into mechanisms of impaired IL‐7 signaling and function in disease and could be relevant for the study of IL‐7‐based immunotherapeutics. Specifically, this study has linked STAT5 and PI3K activation to shared and distinct IL‐7‐associated activities in human CD8 + T cells.